2009
DOI: 10.1017/s1368980009992102
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in weight reduction behaviour by weight status in schoolchildren

Abstract: Objective: To investigate the relationships between weight reduction behaviour among non-overweight schoolchildren and dietary habits, perception of health, well-being and health complaints. Design: Analysis of the 2006 Health Behaviour in School-aged Children survey, a cross-sectional study involving schoolchildren aged 10-17 years. Setting: Schools in the Republic of Ireland. Results: The proportion of children (n 3599) engaged in weight reduction behaviour ('dieting' among non-overweight students) was 10?3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 81 publications
3
12
0
Order By: Relevance
“…In general, although overweight adolescents are more likely than their non‐overweight peers to report dieting and UWCB, these behaviours are also prevalent in non‐overweight youth (Crow et al, ; Kelly et al, ; Kim & Kim, ; López‐Guimerà et al, ; Neumark‐Sztainer & Hannan, ; Neumark‐Sztainer et al, ). Therefore, it is important that youth of all weight groups be included in efforts aimed at preventing the use of unhealthy behaviours to control or lose weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, although overweight adolescents are more likely than their non‐overweight peers to report dieting and UWCB, these behaviours are also prevalent in non‐overweight youth (Crow et al, ; Kelly et al, ; Kim & Kim, ; López‐Guimerà et al, ; Neumark‐Sztainer & Hannan, ; Neumark‐Sztainer et al, ). Therefore, it is important that youth of all weight groups be included in efforts aimed at preventing the use of unhealthy behaviours to control or lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of these behaviours is cause for concern, given that results from a broad range of studies indicate that dieting and UWCB are associated with less healthy dietary patterns and may have a negative effect on both physical and psychosocial health (Crow, Eisenberg, Story, & Neumark‐Sztainer, ; French & Jeffery, ; Goldschmidt et al, ; Guest et al, ; Kelly, Molcho, & Gabhainn, ; Larson, Neumark‐Sztainer, & Story, ; Neumark‐Sztainer, Hannan, Story, & Perry, ; NeumarkSztainer, Story, Beth, Resnick, & Blum, ; Rawana, Morgan, Nguyen, & Craig, ; Santos, Richards, & Bleckley, ; Stice & Bearman, ; Tomiyama et al, ; Turner et al, ). In addition, longitudinal studies indicate that engaging in unhealthy and extreme weight‐control behaviours increases risk for weight gain, overweight status, disordered eating behaviours and the development of clinical eating disorders (Field et al, ; Neumark‐Sztainer et al, ; Neumark‐Sztainer et al, ; Neumark‐Sztainer, Wall, Story, & Sherwood, ; Patton et al, ; Patton, Selzer, Coffey, Carlin, & Wolfe, ; Stice, Cameron, Killen, Hayward, & Taylor, ; Stice, Presnell, Shaw, & Rohde, ).…”
Section: Introductionmentioning
confidence: 99%
“…For weight reduction, the majority of adolescent girls adopted healthy strategies such as moderate dieting by reducing their meal sizes and snacks, and exercise, which can provide benefits to overweight and obese girls. However, at the same time, some female adolescents used unhealthy strategies to lose weight like skipping meals, fasting, vomiting, or taking diet pills [1,2,5,6,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Several motives for dieting were found in the studies with adolescents. Self-perception of overweight [2,3,5,7,15], lower body satisfaction [6,16-18], and an inaccurate perception of their weight [19] were the motives which drove them to go on a diet.…”
Section: Introductionmentioning
confidence: 99%
“…19 A longitudinal study conducted in Juiz de Fora, Minas Gerais, among 358 students aged 11 to 14 years, showed that the prevalence of body dissatisfaction increased among girls as they grew up, while the opposite was observed among boys. 25 In an evaluation on 3,096 Irish students of healthy weight, Kelly et al 26 29 or weight loss and that they regulated emotions, whereas in reality body dissatisfaction had the power to trigger the start of smoking.…”
Section: Objectivementioning
confidence: 99%